PENGARUH REPUTASI KAP DAN FEE AUDIT TERHADAP KUALITAS AUDIT (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2017-2019) - Herdiyana, Mita Budi; Prabowo, Tri Jatmiko Wahyu (Diponegoro Journal of Accounting, 2021)
The purpose of this research is to examine the effect between Public Accounting Firm reputation and audit fees to audit quality by using a proxy of discretionary accruals of the company. The dependent variable in this study is audit quality. Meanwhile, the independent variables in this study were KAP reputation and audit fees.In this study using secondary data sources. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange in 2017-2019. The samples in this study consisted of 49 manufacturing companies obtained by purposive sampling method. This research hypothesis testing method uses multiple regression analysis. The results of this study indicated that Public Accounting Firm’s reputation does not a significant effect on audit quality. Meanwhile, the audit fee has a significant positive effect on audit quality.